Penguatan Karakter Mahasiswa Melalui Mata Kuliah Bahasa Indonesia - Lilik Herawati (Nuances of Indonesian Language, 2021)
This research aims to describe the strengthening of student character in Indonesian courses including planning, implementation, assessment, inhibiting factors, and support. This type of research is descriptive qualitative. The subject of this research is a lecturer who teaches Indonesian language courses. Data obtained through observation, interviews, and documentation analysis. Data analysis used the Miles and Huberman analysis model. The results obtained, that character education has been integrated in Indonesian language learning, both in planning, implementation, and learning assessment. At the learning planning stage, Indonesian language lecturers have included character values that will be implemented in learning in the syllabus and RPS. The implementation of Indonesian language learning as a whole has implemented character values.  Assessment of Indonesian language learning based on the RPS made by Indonesian language lecturers includes affective, cognitive, and psychomotor assessments. Assessment is carried out through observation, questions, and classical discussions. Inhibiting factors for the integration of character strengthening for students in Indonesian language learning, that  is lecturers having difficulty in choosing character values and integrating them with learning materials, assessing the achievement of character education, and learning media that are less supportive. Supporting factors for the integration of character strengthening in Indonesian language learning, that is the campus environment, interactions between students, and a coherent teaching schedule.